Data on the bumblebee assemblages (Apidae: Bombus spp.) lives in lands under agri-environment commitment - Arnóczkyné Jakab, Dóra; Nagy, Antal (Acta Agraria Debreceniensis, 2019)
The goal of agri-environmental schemes (AES) and greening programs are protecting and increasing biodiversity in agricultural lands. The evaluation of effectiveness of AES needs further investigations. For the purpose of investigations, species and species groups should be selected which can indicate the effects of changes in landscape use on biodiversity. Bumblebees are good indicators for this purpose.The role of bumblebees in pollination is well studied but in the case of different crops, much less detailed data are available. In 2018, bumblebee assemblages of 44 sites belonged to 8 different agricultural and semi-natural habitat types were studied in the surroundings of Sajószöged, Tiszaújváros and Derecske.This study provides new distribution data of 8 bumblebee species in three 10×10 km UTM cells covering the sampling area. According to our results, the alfalfa and red clover fields and semi-natural grasslands has more species rich and abundant bumblebee assemblages than different crop fields (sunflower, oilseed radish and vegetable morrow) and can help protect bumblebee assemblages of agricultural lands. Based on the collected distribution and abundance data, the role of the bumblebees in pollination of the studied crops should be re-evaluated.